Modeling stochastic inflow patterns to a reservoir with hidden phase-type Markov model - M. L. Gamiz; D. Montoro-Cazorla; M. C. Segovia-Garcia (Environmental and Ecological Statistics, 2026)
This paper proposes a new statistical framework for modeling precipitation patterns in a specific geographic region using Hidden Markov Models (HMMs). Unlike conventional HMMs, where the hidden state process is Markovian, our approach introduces non-Markovian behavior by incorporating phase-type distributions to model state durations. This extension allows for a more realistic representation of alternating dry and wet periods, providing deeper insight into the temporal structure of the local climate. Building on this framework, we model reservoir inflow patterns linked to the hidden states and explain observed water storage levels through a Moran model. The analysis uses historical rainfall and inflow records, where inflows are influenced by latent climatic conditions rather than rainfall alone. By integrating these unobserved dynamics, the proposed model captures system complexity that would be missed by direct observation-based modeling. To evaluate performance, we compare our model against several standard ARIMA alternatives. The proposed PH-HMM achieves a substantially lower AIC (204.38) than the best ARIMA specification (211.91) and reduces mean squared error from 185.74 to 183.10. These improvements demonstrate that explicitly modeling regime dynamics yields more accurate and parsimonious representations of inflow processes. Overall, the methodology enhances characterization of underlying climatic regimes and improves inflow modeling, offering a practical tool for water resource management and climate adaptation planning.

Zeolite@Metal-organic framework core-shell synthesized from the aluminum of the zeolite with accessible internal surface for CO2 adsorption - Lucas Güemes; Marta Navarro; Fernando Cacho-Bailo; Cristian D. Jaimes-Paez; Diego Cazorla-Amorós; Carlos Téllez; Joaquín Coronas (Chemical Engineering Journal, 2025)

Activated carbons for flow electrode capacitive deionization (FCDI) – Morphological, electrochemical and rheological analysis - H.M. Saif; B. Ferrández-Gómez; V.D. Alves; R.M. Huertas; G. Alemany-Molina; A. Viegas; E. Morallón; D. Cazorla-Amorós; J.G. Crespo; S. Pawlowski (Desalination, 2025)

Catalytic nitrate reduction using a Pd-Cu catalysts supported on carbon materials with different porous structure - D.T. González; J.A. Baeza; G. Alemany-Molina; L. Calvo; M.A. Gilarranz; E. Morallón; D. Cazorla-Amorós (Journal of Environmental Chemical Engineering, 2025)

Fe-Nx biomass-derived carbon material as efficient cathode electrocatalyst for alkaline direct methanol fuel cells - G. Alemany-Molina; V. Baglio; S. Campagna Zignani; A.S. Aricò; E. Morallón; D. Cazorla-Amorós; C. Lo Vecchio (Chemical Engineering Journal, 2025)

Optimization of the Polarized Imaging Nephelometer (PI-Neph) for continuous monitoring of multiwavelength aerosol phase functions in support of space polarimetry missions - E. Bazo; J.V. Martins; D. Perez-Ramirez; A. Valenzuela; G. Titos; A. Cazorla; D. Fuertes; M. Weiss; A. Turpie; C. Li; F.J. García-Izquierdo; I. Foyo-Moreno; et al. (Atmospheric Environment, 2024)

Cloud condensation nuclei activation properties of Mediterranean pollen types considering organic chemical composition and surface tension effects - A. Casans; F. Rejano; J. Maldonado-Valderrama; J.A. Casquero-Vera; S. Ruiz-Peñuela; B.L. van Drooge; H. Lyamani; A. Cazorla; E. Andrews; Jack J. Lin; F. Mirza-Montoro; D. Pérez-Ramírez; et al. (Atmospheric Environment, 2023)

Characterization of Tajogaite volcanic plumes detected over the Iberian Peninsula from a set of satellite and ground-based remote sensing instrumentation - V. Salgueiro; J.L. Guerrero-Rascado; M.J. Costa; R. Román; A. Cazorla; A. Serrano; F. Molero; M. Sicard; C. Córdoba-Jabonero; D. Bortoli; A. Comerón; F.T. Couto; et al. (Remote Sensing of Environment, 2023)

Innate immune response of rainbow trout erythrocytes to spinycterins expressing a downsized viral fragment of viral haemorrhagic septicaemia virus - S. Puente-Marin; D. Cazorla; V. Chico; J. Coll; M. Ortega-Villaizan (Aquaculture, 2023)

Incorporating Ecosystem Functional Diversity into Geographic Conservation Priorities Using Remotely Sensed Ecosystem Functional Types - B. P. Cazorla; J. Cabello; J. Peñas; P. P. Garcillán; A. Reyes; D. Alcaraz-Segura (Ecosystems, 2021)

Abnormalities in flatfishes of the south‐west Atlantic Ocean - D. L. Castellini; M. González‐Castro; A. Lopez‐Cazorla; J. M. Díaz De Astarloa (Journal of Fish Biology, 2018)
Five adult paralichthyid specimens with various kinds of abnormalities are reported from the south‐west Atlantic Ocean. These abnormal flatfish specimens represent the first records of wholly ambicoloured Paralichthys orbignyanus specimens having a deep notch between the eye and dorsal fin and a partially albinistic specimen having skeletal deformities and only the second record of an almost totally ambicoloured specimen. We also report the first observation of reversal in Paralichthys patagonicus and an almost totally ambicoloured, reversed Xystreurys rasile .

Biological control of avocado white root rot with combined applications of Trichoderma spp. and rhizobacteria - D. Ruano-Rosa; F. M. Cazorla; N. Bonilla; R. Martín-Pérez; A. De Vicente; C. J. López-Herrera (European Journal of Plant Pathology, 2014)

Q fever osteoarticular infection: four new cases and a review of the literature - C. Landais; F. Fenollar; A. Constantin; C. Cazorla; C. Guilyardi; H. Lepidi; A. Stein; J. M. Rolain; D. Raoult (European Journal of Clinical Microbiology & Infectious Diseases, 2007)